Requirements of professional development for science teachers in intermediate stage during Covid-19 pandemic - Alzughibi, Ghader Ali (Journal of Educational and Psychological Sciences, 2022)
This study aims to identify the most important requirements of professional development for middle school science female teachers under the coronavirus (COVID-19) pandemic from the viewpoint of female teachers working in Medina, and also to reveal the effect of the following variables (academic qualification, years of experience, and number of training courses) on the research sample response. For this purpose, the descriptive survey approach was used in addition to the questionnaire tool to collect information. This tool was applied to the research sample that was consisted of (224) female teachers. The study findings showed a high degree of agreement in terms of the three themes in question, with an arithmetic mean of (4.16) for the professional development requirements theme related to the implementation of lessons, with an arithmetic mean of (4.05) for the professional development requirements theme related to the evaluation of lessons, and with an arithmetic mean of (4.00) for the professional development requirements theme related to the field of learning management. They also showed that, as for the implementation of lessons theme, the most important requirements of professional development were the need for training to use all the potentials and means available on the Madrasty platform, and also the most important requirements were the need to (design/use electronic applications and software to correct assignments and essay tests); and as for the theme of learning management, the most important requirements of professional development were the need to (design/use applications and software to monitor the female student’s performance of assignments and homework). Moreover, the findings showed that there were statistically significant differences that were due to the academic qualification, in the themes of implementation and evaluation of lessons; in the themes of evaluation of lessons and learning management; and there were no statistically significant differences that were due to the number of instructional training courses. In light of these findings, the study recommends the need to develop the skills of technical science female teachers, as these skills increase their ability to employ technology in implementing and evaluating lessons and managing learning to face future urgent challenges.